Association of the IL-6R rs2228145 polymorphism with diabetic nephropathy: A case-control study - Izakovicova, Pavla; Slezakova, Simona; Deissova, Tereza; Poskerova, Hana; Borilova Linhartova, Petra; Dusek, Ladislav; Kankova, Katerina; Izakovicova Holla, Lydie (Journal of diabetes investigation, 2025)
INTRODUCTION: The pathogenesis of diabetes mellitus (DM) and its complications has been previously linked to elevated levels of interleukin-6 (IL-6); IL-6 triggers intracellular pathways through interaction with the IL-6 receptor (IL-6R). This study aimed to determine the association of single nucleotide polymorphisms (SNPs) IL-6 -597G/A (rs1800797), -572G/C (rs1800796), -174G/C (rs1800795), its receptor (IL-6R) Asp358Ala (+48892A/C, rs2228145) and DM or its complications in the Czech population. MATERIALS AND METHODS: In total, 669 subjects participated in this case-control study, including 167 controls, 119 patients with type 1 DM (T1DM), and 383 patients with type 2 DM (T2DM). The subjects were monitored for glycemia, glycated hemoglobin, lipid profile, glomerular filtration rate (GFR), and common complications, such as diabetic nephropathy (DN), retinopathy (DR), (poly)neuropathy (DPN), and periodontitis (P). RESULTS: Frequencies of the IL-6 and IL-6R alleles or genotypes, and IL-6 haplotypes were similar between the controls and the patients with T1DM or T2DM (P > 0.05). However, lower values of GFR were observed in diabetic patients with IL-6 -174CC homozygotes compared to other (CG and GG) genotypes (P ≤ 0.05). In addition, the IL-6R Asp358Ala variant was associated with DN (P = 0.031, OR = 1.74, 95% CI: 1.05-2.89). After subclassification according to the type of DM, the significant association of the IL-6R polymorphism with DN was only found in T1DM (P = 0.013, OR = 2.90, 95% CI: 1.25-6.71). CONCLUSIONS: This study implies a significant relationship between the IL-6R Asp358Ala polymorphism and DN in Czech T1DM patients.
Keywords: Interleukin-6; lidé; Middle Aged; Adult; Diabetic nephropathy; Case-Control Studies; Polymorphism, Single Nucleotide; Female; Polymorphisms; jednonukleotidový polymorfismus; diabetes mellitus 1. typu; Humans; Diabetic Nephropathies; diabetické nefropatie; interleukin-6; Genotype; studie případů a kontrol; Česká republika; Diabetes Mellitus, Type 1; lidé středního věku; diabetes mellitus 2. typu; mužské pohlaví; Diabetes Mellitus, Type 2; genetická predispozice k nemoci; Czech Republic; ženské pohlaví; genotyp; Male; Aged; receptory interleukinu-6; Receptors, Interleukin-6; dospělí; Genetic Predisposition to Disease; IL‐6; senioři